2022
DOI: 10.2147/orr.s294369
|View full text |Cite
|
Sign up to set email alerts
|

Where are We Now and What are We Hoping to Achieve with Robotic Total Knee Arthroplasty? A Critical Analysis of the Current Knowledge and Future Perspectives

Abstract: Robotic-assisted total knee arthroplasty (rTKA) has been developed to improve knee kinematics and functional outcomes, expedite recovery, and improve implants long-term survivorship. Robotic devices are classified into active, semi-active, and passive, based on their degree of freedom. Their capacity to provide increased accuracy in implants positioning with reduced radiographic outliers has been widely proved. However, these early advantages are yet to be associated with long-term survivorship. Moreover, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Buchlak et al 38 found that robot-assisted TKA was associated with a shorter operative duration, a higher likelihood of achieving the target alignment, and a shorter length of stay than computer-navigated TKA. A critical analysis review showed that robot-assisted TKA provided more accurate and precise implant positioning, potentially leading to better long-term outcomes 39 . Similarly, another review concluded that robot-assisted TKA was superior to computer-navigated TKA in terms of the accuracy and precision of implant placement, with a significantly lower rate of outliers 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Buchlak et al 38 found that robot-assisted TKA was associated with a shorter operative duration, a higher likelihood of achieving the target alignment, and a shorter length of stay than computer-navigated TKA. A critical analysis review showed that robot-assisted TKA provided more accurate and precise implant positioning, potentially leading to better long-term outcomes 39 . Similarly, another review concluded that robot-assisted TKA was superior to computer-navigated TKA in terms of the accuracy and precision of implant placement, with a significantly lower rate of outliers 40 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been concerns of several complications associated with RA-TKA tracker pin site including superficial infections, osteomyelitis, stress fracture, vascular injury, hematoma, myositis ossificans, and mechanical failures [ 17 , 20 ]. While one patient in this study in RA-TKA group did have a peri-prosthetic fracture in first operated knee, it is less likely to be attributed to the pin tract of robotic tracker as the fracture pattern was intraarticular and did not involve pin tract site and was associated with history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic technology use in total knee arthroplasty (TKA) has been introduced to improve the accuracy of implant positioning and achieving target limb alignment in order to reduce residual pain, improve patient satisfaction, and implant survivorship [ 9 ]. Previous studies on robotic-assisted TKA (RA-TKA) reported improved accuracy in achieving planned coronal alignment, joint line restoration, and posterior tibial slope (PTS) as compared to conventional TKA (C-TKA) using intramedullary instruments for bone cuts [ 17 ]. Despite this improvement in accuracy of implant positioning, RA-TKA has not shown improvement in patient-reported outcomes (PROs) and implant survivorship over C-TKA [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such case is the NAVIO (Smith & Nephew, UK), used in TKA ( Wu et al, 2021 ). This is a handheld tool that can either limit the speed of the surgical burr tooltip, or completely block the burr itself upon penetrating the boundary ( Mancino et al, 2022 ). Cadaveric study results on TKA for the NAVIO demonstrated a mean femoral flexion of 2.0° ( Casper et al, 2018 ), which is an improvement compared to standard methods.…”
Section: Introductionmentioning
confidence: 99%